The exceptional photofermentative hydrogen metabolism of the green alga Chlamydomonas reinhardtii. (1st February 2005) - Hemschemeier, A.; Happe, T.
Abstract : The photosynthetic green alga Chlamydomonas reinhardtii is capable of performing a complex fermentative metabolism which is related to the mixed acid fermentation of bacteria such as Escherichia coli . The fermentative pattern includes the products formate, ethanol, acetate, glycerol, lactate, carbon dioxide and molecular hydrogen (H2 ). H2 production is catalysed by an active [Fe]-hydrogenase (HydA) which is coupled with the photosynthetic electron-transport chain. The most important enzyme of the classic fermentation pathway is pyruvate formate-lyase, which is common in bacteria but seldom found in eukaryotes. An interaction between fermentation, photosynthesis and H2 evolution allows the algae to overcome long periods of anaerobiosis. In the absence of sulphur, the cells establish a photofermentative metabolism and accumulate large amounts of H2 .